Edification - Senathirajah, Pathman; VStudios ([S.l.] : VStudios, 2008)
Edification is a token gesture of respect, admiration, trust and faith that the V practices to empower leadership. As part of the four pillars of success, edification is a skill worth learning and doing in order to build a bigger, stronger business
Title from title screen
DVD format
Keywords: Multilevel marketing; Direct marketing